Optimalisasi Pembelajaran di Desa Wungurejo melalui Program Pendampingan Pendidikan oleh Mahasiswa KKN Posko 50 - Eriana Salma Rusda; Clarista Marya Ulfa; Uni Zulfa; Ulfatun Tazkiyah; Laila Denianti; Siti Nuriya Ulha Fatiha; Ahmad Irfan; Ahmad Daelal Firoos; Izantri Sepja Tara (Lembaga Pengembangan Kinerja Dosen, 2024)
This study evaluates the educational assistance program carried out by KKN Post 50 students from UIN Walisongo Semarang in Wungurejo Village, Kendal, with the aim of improving the quality of education and children's learning motivation. This program includes various activities such as KKN Teaching, Scholar Village, and KKN Edu-Competition, which adopts the Participatory Learning and Action (PLA) method to encourage active interaction between students and the community. Despite the challenges of equal distribution of participants, activities such as calligraphy and smart learning succeeded in attracting the interest of children, who felt that it was helpful in understanding the subject matter and was more motivated to learn. Positive responses from parents and teachers show that the presence of KKN students contributes to overcoming the shortage of educators and increasing children's enthusiasm for learning. The results of the evaluation show that this activity is effective and has a positive impact, and it is hoped that it can continue to be developed to improve the quality of education in the village.